Leviticus - Kamionkowski, S. Tamar (Wisdom commentary, 2018)
Author's Introduction: Reading Leviticus with a Feminist Lens -- Leviticus 1:1-3:17 Offerings, Offerers, and Considerations of Gender -- Leviticus 4:1-6:7 Something New: Purification and Guilt -- Leviticus 6:8-7:38 Another Perspective on Offerings, or What's In It for the Priests? -- Leviticus 8:1-10:20 Coming Into and Managing Power -- Leviticus 11:1-47 If You Must Eat Meat, Then ... -- Leviticus 12:1-15:33 Bodies and Access to the Holy -- Leviticus 16:1-34 Purifying the Sancta: "It Takes a Village" -- Leviticus 17:1-16 A Bloody Mess -- Leviticus 18:1-20:27 From Ritual Impurity to Ethical Transgressions -- Leviticus 21:1-22:33 Protecting Priestly Privilege -- Leviticus 23:1-25:55 Sacred Time, Space, Speech, and Land -- Leviticus 26:1-46 Eco-Friendly Blessings and Curses of Chaos -- Leviticus 27:1-34 How Much Is a Woman Really Worth? -- Postscript